Microwave synthesis of carbon onions in fractal aggregates using heavy oil as a precursor - Adam, Mohamed; Hart, Abarasi; Stevens, Lee A.; Wood, Joseph; Robinson, John P.; Rigby, Sean P. (Elsevier, 2018)
In this work we report a method for preparing carbon onions through microwave heating of heavy oil. It was shown that microwave heating of heavy oil mixed with a carbon catalyst at 300 W leads to the growth of a several-centimetre long fractal carbon structure in just 60 s. Scanning electron microscopy (SEM) images showed that the structure is predominantly made of networks of small particles with diameters ranging from tens to hundreds of nanometres. High-resolution transmission electron microscopy (HRTEM) images revealed the presence of disordered graphitic structures, including carbon onions with diameters as small as 30 nm. This was supported by the Raman spectroscopy which showed typical spectra for carbon onions with disordered graphitic structure. CO2 gas sorption results revealed a specific surface area of up to 164 m2/g. The carbon onions are believed to form through pyrolysis of the oil into light hydrocarbons followed by nucleation and growth of concentric graphitic layers. The carbon tree, subsequently, grew through aggregation of the carbon onions and further deposition of pyrolytic carbon, with the electric field configuration favoured the longitudinal growth of thin branches. This study demonstrates that carbon onions can be prepared from cheap unrefined liquid precursors.